Commercial uses of space and space tourism : legal and policy aspects - Wouters, Jan, 1964-; Man, Philip de; Hansen, Rik (Leuven global governance, 2017)
Commercial Uses of Space and Space Tourism combines the perspectives of academics, policy makers and major industry players around three central themes: the international legal challenges posed by the dramatic changes to the spacefaring landscape; the corresponding legal and regulatory responses to these challenges at the national level; and topical questions of global space governance. Chapters cover emerging activities in commercial spacefaring, including space tourism and space transportation, and identify the regulatory issues that may arise in the absence of a clear boundary between airspace and outer space. By taking a pragmatic, inductive approach, the book aims to breathe new life into the discussion of the air-space boundary, while informing readers about the many exciting recent developments in commercial spacefaring. This book will appeal to lecturers, academics and students in space law and air law, as well as policy makers and industry practitioners involved in the regulation of orbital and suborbital commercial spaceflight, both manned and unmanned.